Political will in disaster mitigation and response initiatives a comparative studies between Kelantan, Malaysia and Jigawa, Nigeria - Halim, Nurulhazany; Aliyu, Kehinde Adekunle (2016)
The incessant occurrences of natural and human induced disasters have become a serious menace to the World most especially in the developing countries or societies. The low level of technological know-how employed to combat disasters adds to the problem. This paper looks at the implication of lack of political will using unpolished and inaccessible methods of managing risks and disasters in both rural and urban areas of the two selected places in Malaysia and Nigeria at the expense of cheap, reliable, precise method of management and remote sensing technologies. The aim of this work is to compare the political will of the government on disaster management and asserting the roles of government and social workers in assisting the victims. Mixed method research design was adopted for the work. Data collected with the secondary data and interview Schedule for the affected community people. This was administered to a group of people in both country, which comprises both male and female in the Kelantan and Jigawa both in Malaysia and Nigeria respectively.The researcher conducted an experiment (quantitative) and after the experiment conduct an interview study with the participants (qualitative) to see how they viewed the experiment and to see if they agreed with the results.The focus of the data collection was on the roles of government regarding the mitigation of disaster in the two community and family welfare.The purpose of the study was to compare the responsiveness of the both countries governments and to show how both can learn from each other’s mistake and generally learn from developed countries.To a huge risk connected with the incapability of people to manage hazards and disasters that may finally lead to undesirable magnitudes like destruction of the environment, socioeconomic activities, loss of lives and property.